2012
DOI: 10.1007/s00167-012-2200-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ratios of lateral to medial patellofemoral forces and pressures after lateral retinacular release and gender knees in total knee arthroplasty

Abstract: Use of lateral to medial patellofemoral force ratios as a surrogate objective marker for patellar tracking was validated in this study by decreasing ratios observed after lateral release in TKA and with gender-specific implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…21,22 Meanwhile, LRR can achieve improved patellar tracking and thus decreases retropatellar contact pressure. 8,9 Therefore, the performance of intraoperative LRR may reduce AKP after TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Meanwhile, LRR can achieve improved patellar tracking and thus decreases retropatellar contact pressure. 8,9 Therefore, the performance of intraoperative LRR may reduce AKP after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Circumpatellar electrocautery (CE) can damage the innervation of the peripatellar soft tissues and thus reduces postoperative AKP. 1 Lateral retinacular release (LRR) can improve patellar tracking and decrease retropatellar pressure, 8,9 which may lead to a low incidence of postoperative AKP. However, the efficacy of both techniques is controversial because regardless of the use of LRR or CE, the incidence of AKP after TKA remains high.…”
mentioning
confidence: 99%
“…Lateral retinacular release is most commonly performed on knee arthroplasties with valgus deformity to improve joint congruity, 51 , 52 , 53 , 54 , 55 decreasing the incidence of anterior knee pain, especially if the patellar component is not performed. 52 , 56 With TKA, the forces and peak pressures significantly increase in the patellofemoral joint, and lateral release may reduce the ratio of these forces and pressure in this region, 8 , 54 , 57 , 58 with low rates of complications. 51 , 55 , 56 …”
Section: Lateral Retinacular Release In Tkamentioning
confidence: 99%
“…11 A correct soft tissue balance is the most important factor for the durability of the prosthesis and improper release of the medial collateral ligament (MCL) may result in pain, deteriorated patellofemoral biomechanics, joint stiffness, tibiofemoral instability, polyethylene wear, osteolysis, aseptic loosening, and early implant failure. [12][13][14][15] Also, excessive soft tissue release can lead to significant mediolateral instability, and an unbalanced flexion and extension gap that may necessitate the use of a constrained prosthesis. [16][17][18] This may be a reason for the recommendation that for all TKAs without navigation or using kinematic alignment, soft tissue release must be performed and include a supporting reference for kinematic alignment not using soft tissue releases, while some authors reported only in 50 to 88% of TKAs, collateral ligament needs to be released.…”
mentioning
confidence: 99%
“…15.7%] vs. 193 females [84.3%]) with the mean age of 66.7 AE 7.93 (range ¼ 42-92). The TKA was performed on the left and right side in 129 (56.3%) and 100 (43.7%), respectively.…”
mentioning
confidence: 99%